2021
DOI: 10.1002/hep.31898
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Significantly Enhances Induction of Induced Pluripotent Stem Cells to Endoderm by Enhancing Survival Through Protein Kinase B Phosphorylation

Abstract: Background and Aims Induced pluripotent stem cells (iPSCs) provide an important tool for the generation of patient‐derived cells, including hepatocyte‐like cells, by developmental cues through an endoderm intermediate. However, most iPSC lines fail to differentiate into endoderm, with induction resulting in apoptosis. Approach and Results To address this issue, we built upon published methods to develop an improved protocol. We discovered that doxycycline dramatically enhances the efficiency of iPSCs to endode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Especially during the first day of CHIR99021-and Activin A treatment, a lot of cell death has been observed, probably due to the drastic change in medium and Activin A and CHIR concentration ( Peaslee et al, 2021 ). Nonetheless, after the first wave of cell death, massive cell proliferation takes place, demanding fine-tuning of the initial cell number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially during the first day of CHIR99021-and Activin A treatment, a lot of cell death has been observed, probably due to the drastic change in medium and Activin A and CHIR concentration ( Peaslee et al, 2021 ). Nonetheless, after the first wave of cell death, massive cell proliferation takes place, demanding fine-tuning of the initial cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we recommend testing the initial cell number for each cell line, as the DE outcome is indispensable for successful further differentiation. Peaslee et al found that doxycycline can help to prevent apoptosis during the first Activin A incubation ( Peaslee et al, 2021 ). Even though there was no direct effect on HLC-marker expression, they saw a general improvement in their HLC-culture with a more defined monolayer and better viability.…”
Section: Discussionmentioning
confidence: 99%
“…iPSCs were differentiated into hepatoblasts as previously published. 1 Expression of hepatocyte-specific markers albumin and hepatic nuclear factor 4 alpha (HNF4A) were confirmed by fluorescence-activated cell sorting at a threshold of >90% dual-positive cells.…”
Section: Supplementary Materials and Methodsmentioning
confidence: 98%
“…We next compared the degree of oleate-induced lipid accumulation in iPSCs from 8 donors both in their undifferentiated state and after differentiation into iPSC-Heps through a 23-day protocol as we previously described. 6 iPSC-Heps were authenticated by expression of hepatocyte markers and secretion of albumin into the culture media ( Supplemental Figure 1 , A‒B ). There were no differences in the levels of intracellular lipids in the isogenic iPSCs and iPSC-Heps, either with values expressed as absolute levels or the magnitude of change between oleate vs. BSA treated cells ( Supplemental Figure 1 , C‒E ).…”
mentioning
confidence: 99%
“…In addition to upregulating the expression of liver-specific genes, enhancing differentiation efficiency at each stage of the hepatocyte differentiation process is also important for the production of hepatocytes. In this regard, it was discovered that doxycycline increased the efficiency of endoderm differentiation by preventing apoptosis and did so via the protein kinase B pathway during the differentiation of iPSCs into endoderm, but that there was no appreciable difference in gene expression and phenotype relative to hepatocytes generated without the induction of doxycycline [64,65].…”
Section: Role Of Other Additives In Inducing Ipsc Differentiation Int...mentioning
confidence: 99%